Complexos difenil-pirazólicos de platina: estrutura, interação com biomoléculas e citotoxicidade - Ana Luiza de Andrade Querino (2020)
Platinum(II)-based drugs are well known and widely used in cancer chemotherapy since the serendipitous discovery of the antitumor properties of cisplatin. However, toxic side effects and intrinsic or acquired cell resistance by some patients under cisplatin treatment can compromise its efficacy and have been stimulating the search for analog compounds with a more promising effects profile. This work presents the synthesis and structural characterization of platinum complexes of general formula [PtII(Pz)2Cl2], where Pz are diphenyl-pyrazole derived ligands, aiming to obtain potential antitumor agents. Pyrazole heterocycle derivatives are biologically relevant for their wide range of bioactivities reported in the literature. The diphenyl-pyrazole ligands used in this work have structure modifications on aryl groups, one is a para-fluorophenyl and the other phenyl is para-substituted by R groups (-CH3, -F or -Cl), L1, L2 e L3 respectively, in order to investigate their structure-activity relationships. The complexes were characterized by elemental, conductivity and thermogravimetric analysis, FTIR, electronic, NMR and mass spectrometry, as well as single-crystal X-ray diffraction. The interaction of synthesized compounds with DNA and BSA through spectrophotometric assay was also evaluated, resulting in similar or superior binding ability compared to the free ligands. In addition, agarose gel electrophoresis with plasmid DNA revealed that complexes are capable of interaction with DNA and modify its electrophoretic mobility. Antiproliferative activities were assessed against tumor (B16F10 and 4T1) and non-tumor (BHK21) cell lines, and the cytotoxicity of the compounds was strongly increased after metal complexation displaying promising activity, especially complexes C1 and C3, despite its low selectivity. It was also assessed the ability of BSA and GSH biomolecules to decrease the cytotoxicity of the complexes against B16F10. It can be highlighted here that the C3 activity was not disturbed in those conditions. Lastly, complexes were properly obtained and bioinorganic analysis suggest that C3 has better interaction with DNA (the main biological target), managing to circumvent biomolecules such as BSA and GSH that can cause its deactivation.